Environmental Impact Assessment (EIA) in the Arctic - Koivurova, Timo (Routledge, 2017)
This title was first published in 2002. This volume examines the norms of international law that apply to the planning stage of large-scale activities such as hydrocarbon exploitation, mineral extraction and forestry. These stationary activities (those that remain at a single location for a period of time), pose grave risks to the Arctic environment, since the development of technology has made it profitable to exploit natural resources even in such harsh regions.